Treatises on Solvency II - Dreher, Meinrad (Springer, 2016)
The European system of insurance supervision under Solvency II constitutes a parallel to supervision of credit institutions under Basel III. At the heart of this new European insurance supervisory regime are the Solvency II Directive, the attendant regulation, and the EIOPA Regulation. The present volume, "Treatises on Solvency II", includes articles on the bases of European insurance supervision and the associated three pillars of solvency, governance, and disclosure, all viewed predominantly from a legal standpoint.